Diversity of arbuscular mycorrhiza spores under Shorea balangeran (Korth.) Burck. plantation as bioindicator for the revegetation success - Tri Wira Yuwati; Wanda Septiana Putri (Jurnal GALAM, 2020)
Arbuscular mycorrhiza is an association between fungi and plantroots. Arbuscular mycorrhiza has many functions such as improving the plant’s growth, increasing the absorption of soil nutrients and enhancing the plants tolerant to extreme condition. Tumbang Nusa Forest for Specific Purpose is a peat swamp forests in Central Kalimantan that was severely burnt in 2015. Peat land rehabilitation program has started since 2016, by Shorea balangeran (Korth.) Burck planting. The aim of this research was to determine the diversity of arbuscular mycorrhiza spores under S. balangeran tree. The results showed that there was relationship between the age of S. balangeran and number of spores. Moreover, there were 4 spores of arbuscular mycorrhiza identified as Glomus sp., Gigaspora sp., Acaulospora sp. and Scutellospora sp